The Effect of Chicken Manure and Mycorrhizal Biofertilizer on Increasing Peanut (Arachis Hypogaea L.) Production Growth - Meriaty; Irawaty Rosalyne (Jurnal Penelitian Pendidikan IPA, 2025)
This study used a factorial Randomized Block Design (RAK), with 2 treatment factors, factor I is the provision of Chicken Manure consisting of 3 treatment levels, namely: K1 = 3 Kg / plot, K2 = 4 Kg / plot, K3 = 5 kg / plot. Factor II is the provision of Mycorrhizal Fertilizer consisting of 4 treatment levels, namely: M0 = Without the provision of Mycorrhizal Biofertilizer, M1 = 2 g / plot, M2 = 4 g / plot, M3 = 6 g / plot. The parameters observed in this study include: Plant Height (cm) 21, 35, and 49 DAP, Number of Primary Branches (branches) when the flowering period has finished, Number of Pods per Plant (pods), Percentage of Full Pods per Plant (%), Seed Production per plot (g). Based on the results of the study, it can be concluded that the treatment of chicken manure dose level significantly affected plant height at the age of 21, 35, and 49 DAP, but did not significantly affect the number of primary branches, number of pods per plant, percentage of full pods per plant, seed production per plot. The treatment of mycorrhizal fertilizer dose level significantly affected plant height at the age of 21, 35, and 49 DAP, number of primary branches, number of pods per plant, percentage of full pods per plant, seed production per plot. For the interaction of chicken manure and mycorrhizal fertilizer treatment significantly affected plant height at the age of 21 DAP, but did not significantly affect plant height at the age of 35 and 49 DAP, number of primary branches, number of pods per plant, percentage of full pods per plant and seed production per plot.